2012
DOI: 10.1002/rsa.20479
|View full text |Cite
|
Sign up to set email alerts
|

Improved inapproximability results for counting independent sets in the hard‐core model

Abstract: Abstract. We study the computational complexity of approximately counting the number of independent sets of a graph with maximum degree ∆. More generally, for an input graph G = (V, E) and an activity λ > 0, we are interested in the quantity ZG(λ) defined as the sum over independent sets I weighted as w(I) = λ |I| . In statistical physics, ZG(λ) is the partition function for the hard-core model, which is an idealized model of a gas where the particles have non-negibile size. Recently, an interesting phase tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 19 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…We will prove here that the convergence of BP provides the existence of a distance function Φ satisfying (7). We defer the technical proof of (6) to Section A of the appendix. The Jacobian J of the BP operator F is given by…”
Section: Path Coupling Distance Functionmentioning
confidence: 95%
See 1 more Smart Citation
“…We will prove here that the convergence of BP provides the existence of a distance function Φ satisfying (7). We defer the technical proof of (6) to Section A of the appendix. The Jacobian J of the BP operator F is given by…”
Section: Path Coupling Distance Functionmentioning
confidence: 95%
“…On the other side, Sly [33] (extended in [6,7,34,8]) has established that, unless N P = RP , for all ∆ ≥ 3, there exists γ > 0, for all λ > λ c (∆), there is no polynomial-time algorithm for triangle-free ∆-regular graphs to approximate the partition function within a factor 2 γn .…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Note that all known approximation algorithms for the partition function of the uniform hard-core model, apply to instances (𝐺, 𝜆), where 𝐺 has maximum degree 𝛥 and 𝜆 < 𝜆 c (𝛥) = (𝛥−1) 𝛥−1 (𝛥−2) 𝛥 ∼ e 𝛥 . This parameter regime is tight, as approximating the partition function for a hard-core model is known to be NP-hard for instances (𝐺, 𝜆) with 𝜆 > 𝜆 c (𝛥) [20,37]. We obtain our algorithms by bounding the maximum degree of 𝐺 𝑋 and using the known approximation algorithms for the hard-core model.…”
Section: Approximation Algorithms Via Canonical Discretizationmentioning
confidence: 99%
“…this line of work culminated in papers by Dyer and Greenhill [5] and Vigoda [29], who gave MCMC based FPRASs for λ < 2/(d − 1) for graphs of maximum degree at most d + 1. Weitz [31] (see also [2]) introduced a new paradigm by using correlation decay directly to design a deterministic FPTAS and gave an algorithm under the condition λ < λ c (d) for graphs of degree at most d + 1; this range of applicability was later proved to be optimal by Sly [26] (see also [7,27]). To date, no MCMC based algorithm is known to have a range of applicability as wide as Weitz's algorithm.…”
Section: Techniquesmentioning
confidence: 99%
“…(Note that the condition on λ is only in terms of the d-ary tree, while the FPTAS applies to all graphs.) This connection to phase transitions was further strengthened by Sly [26] (see also [7,27]), who showed that an FPRAS for the partition function of the hard core model with λ > λ c (d) on graphs of degree d + 1 would imply NP = RP.…”
mentioning
confidence: 92%